PENGARUH METODE OUTDOOR LEARNING TERHADAP KETERAMPILAN MENULIS PUISI SISWA DI KELAS IV UPT SD NEGERI 30 GRESIK - Suci Ramadhanty; Nanang Khoirul Umam; Arya Setya Nugroho (Nusantara Hasana Journal, 2023)
The purpose of this study was to determine the effect of the Outdoor Learning method on Students Poetry Writing Skills in Grade IV UPT SD Negeri 30 Gresik in the 2020/2021 academic year. The research method used in collecting research data is an experimental method with a Pretest - Posttest Control Group Design. The subjects in this study were students in class IV UPT SD Negeri 30 Gresik with a total of 50 students consisting of 25 students in class IVA and 25 students in class 1VB. Data collection techniques and instruments used were validation sheets, observation sheets, validity tests, reliability tests, normality tests, homogeneity tests, T tests and poetry writing skill tests. Based on the analysis of research data, it was found that there was an effect of the Outdoor Learning method on students' poetry writing skills in Class IV UPT SD Negeri 30 Gresik. It is proven by the significant Paired Sample T test in SPSS. Based on the statistical output table, the results obtained are sig (2-tailed) or a probability of 0.034 while the significance level is 0.05 (5%). This shows the probability value is smaller than the significance level (0.034 <0.05) then H0 is rejected and H1 is accepted. This shows that there is an influence of the Outdoor Learning method on students' poetry writing skills